P.075 Clinical spectrum of POLR3-related leukodystrophy caused by biallelic POLR1C pathogenic variants. (5th June 2019) - Gauquelin, L; Cayami, FK; Sztriha, L; Yoon, G; Tran, LT; Guerrero, K; Hocke, F; van Spaendonk, RM; Fung, EL; D'Arrigo, S; Vasco, G; Thiffault, I; et al.
Abstract : Background: Biallelic variants in POLR1C are associated with POLR3-related leukodystrophy (POLR3-HLD), or 4H leukodystrophy (Hypomyelination, Hypodontia, Hypogonadotropic Hypogonadism), and Treacher Collins syndrome (TCS). The clinical spectrum of POLR3-HLD caused by variants in this gene has not been described.Methods: A cross-sectional observational study involving 25 centers worldwide was conducted between 2016 and 2018. The clinical, radiologic and molecular features of 23 unreported and previously reported cases of POLR3-HLD caused by POLR1C variants were reviewed.Results: Most participants presented between birth and age 6 years with motor difficulties. Neurological deterioration was seen during childhood, suggesting a more severe phenotype than previously described. The dental, ocular and endocrine features often seen in POLR3-HLD were not invariably present. Five patients (22%) had a combination of hypomyelinating leukodystrophy and abnormal craniofacial development, including one individual with clear TCS features. Several cases did not exhibit all the typical radiologic characteristics of POLR3-HLD. A total of 29 different pathogenic variants in POLR1C were identified, including 13 new disease-causing variants.Conclusions: Based on the largest cohort of patients to date, these results suggest novel characteristics of POLR1C-related disorder, with a spectrum of clinical involvement characterized by hypomyelinating leukodystrophy with or without abnormal craniofacial development reminiscent of TCS.